2014
DOI: 10.1158/1538-7445.am2014-ct326
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT326: Phase I study of BGJ398, a selective pan-FGFR inhibitor in genetically preselected advanced solid tumors

Abstract: Background: Fibroblast growth factor receptors (FGFRs) play a role in cell proliferation and survival. Genetic alterations of FGFRs can lead to deregulated activation in various cancers, including squamous cell carcinoma (SCC) of the lung and urothelial bladder cancer. Here, we report on a phase I study of BGJ398 a potent, selective pan-FGFR inhibitor. Methods: Eligible patients (pts; ≥ 18 years of age) had tumors with any FGFR genetic alteration identified by central or local prescreening. Pts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 0 publications
3
43
0
Order By: Relevance
“…For example, preliminary analysis of a phase I trial of BGJ398, a potent, selective pan-FGFR inhibitor, showed tumor regression in four of five patients with urothelial carcinomas with FGFR3-activating mutations (with tumor reductions ranging from 27% to 48%; ref. 44).…”
Section: Discussionmentioning
confidence: 99%
“…For example, preliminary analysis of a phase I trial of BGJ398, a potent, selective pan-FGFR inhibitor, showed tumor regression in four of five patients with urothelial carcinomas with FGFR3-activating mutations (with tumor reductions ranging from 27% to 48%; ref. 44).…”
Section: Discussionmentioning
confidence: 99%
“…Third, evidence of oncogene addiction has been reported with highly specific inhibitors in patients with lung cancer and bladder carcinoma presenting FGFR alterations (18,71,74). Clinical benefit and tumor reduction were also reported in patients with glioblastoma and cholangiocarcinoma harboring FGFR translocations, and ongoing trials may help to validate the relevance of these targets.…”
Section: Lessons Learned From the Clinical Development Of Fgfr Inhibimentioning
confidence: 96%
“…Preliminary results (in 94 patients) of the ongoing phase I trial documented clinical benefit in 8 patients with tumors harboring FGFR signaling alterations (4 patients with FGFR1-amplified squamous-NSCLC achieved PRs, and 4 of 5 patients with FGFR3-mutant bladder carcinoma had tumor reductions), 4 of which lasted for more than 16 weeks. In addition, tumor reductions were observed in patients with cholangiocarcinoma with FGFR2 fusion and FGFR1-amplified breast cancer (41,74). AEs were generally mild (grade 2) and included dose-dependent hyperphosphatemia, diarrhea, fatigue, and nausea.…”
Section: Small-molecule Tkis Targeting Fgfrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genomic analyses of lung SCC have also given the first set of potentially targetable driver mutations, including FGFR1, FGFR2, FGFR3, DDR2 and PI3K 20 . Clinical trials that aim to target these subsets of patients who have Stage I-IIIA lung cancers are currently underway; preliminary results were presented at the 2014 American Association for Cancer Research Annual Meeting 86 , and these showed responses to an FGFR inhibitor (BGJ398) in a subset of patients with SCC who have FGFR1 amplification.…”
Section: Current Treatments For Nsclcmentioning
confidence: 99%